Low cardiac and aerobic scope in a coastal population of sockeye salmon Oncorhynchus nerka with a short upriver migration. Issue 6 (15th May 2013) - Eliason, E. J.; Wilson, S. M.; Farrell, A. P.; Cooke, S. J.; Hinch, S. G.
<x xml:space="preserve">Abstract</x> This study showed that a coastal population (Harrison) of Fraser River sockeye salmon Oncorhynchus nerka had a lower aerobic and cardiac scope compared with interior populations with more challenging upriver spawning migrations, providing additional support to the idea that Fraser River O. nerka populations have adapted physiologically to their local migratory environment.